The singles game [compact disc, unabridged] - Weisberger, Lauren, 1977- (Simon & Schuster Audio, 2016)
The new novel from the New York Times bestselling author of The Devil Wears Prada and Revenge Wears Prada. Now comes a dishy tell-all about a beautiful tennis prodigy who, after changing coaches, suddenly makes headlines on and off the court.